Peran Lurah Meningkatkan Kualitas Pelayanan Surat Keterangan Tidak Mampu Di Kelurahan Sumbersari Kota Malang - Noora Fithriana; Merniyasih Tatu Rija; Ronny Ersya Novianto Putra; Firman Firdausi (Journal of Governance Innovation, 2025)
The quality of public service fosters trust between the public and the government. While service personnel are dedicated to their roles, public services provided by the government often fall short of the highest quality. This is particularly true for the issuance of a financial hardship certificate, which requires improvement. At the urban-village administration level, enhancing the quality of public services requires strong leadership from the head. This study aimed to explore the role of the urban-village head of Sumbersari in Malang in improving the quality of public services related to the financial hardship certificate. The research used a qualitative method, gathering primary and secondary data from both verbal and visual sources through various techniques, including semi-structured interviews, observations, and documentation. It could be concluded that the urban-village head of Sumbersari undertaken two critical roles that help improve the quality of service regarding the financial hardship certificate: as an executor and as a director. By fulfilling these roles, the government could enhance the quality of service for the certificate in terms of responsiveness and reliability. Both the roles of the head of the urban village and the quality of service met expectations. The actions taken by the head were numerous and had received positive evaluations. Additionally, there were several sanctions in place when the head neglected his roles in delivering services.